Recent Insights into the Management of Inflammation in Asthma [Letter] - Urakov A; Urakova N (Dove Medical Press, 2021)
Aleksandr Urakov,1,2,* Natalya Urakova1,* 1Department of General and Clinical Pharmacology, Izhevsk State Medical Academy, Izhevsk City, Udmurt Republic, Russian Federation; 2Institute of Applied Mechanics, Udmurt Federal Research Center of the Ural Branch of the Russian Academy of Sciences, Izhevsk City, Udmurt Republic, Russian Federation*These authors contributed equally to this workCorrespondence: Aleksandr UrakovUdmurt Federal Research Center of the Ural Branch of the Russian Academy of Sciences, T. Baramzina Street, 34., Izhevsk City, Udmurt Republic, 426067, Russian FederationTel +79127600939Email urakoval@live.ru View the original paper by Dr Rupani and colleagues